A Comunicação popular comunitária nas ondas do oceano digital: análise do site do Bairro Ellery - Ferreira, Zoraia Nunes Dutra (2012)
This research aims to discuss communication popular community within popular social movements, built and supported by the Internet. The object of study was the chosen site of the neighborhood Ellery (www.bairroellery.com.br). The choice is justified because of the close relationships they had forged earlier by other surveys, the fact that the site of the district Ellery be one of the oldest sites in the neighborhood of Fortaleza, and also by the historic neighborhood has around Community production of popular communication in a context of social struggles. The main objective is to understand the characteristics that communication is replaced when built on a digital platform. Undertook a case study of the site\'s neighborhood looking Ellery, however, consider not only the virtual - the site - but also the concrete, ie, the place where it arose. It interests me a glimpse into the daily production of this media in order to better understand the achievements and challenges of social actors who produce it. The look for the concrete was constructed from the use of the ethnographic method and site analysis, I use a part of this method, the virtual ethnography. Threw hand, still, the use of interviews, opting for anthropological interview.